Automated localisation of optic disc in retinal colour fundus image for assisting in the diagnosis of glaucoma - Listyalina, Latifah; Nugroho, Hanung Adi; Wibirama, Sunu; Oktoeberza, Widhia KZ (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2017)
Optic disc (OD), especially its diameter together with optic cup diameter can be used as a feature to diagnose glaucoma. This study contains two main steps for optic disc localisation, i.e. OD centre point detection and OD diameter determination. Centre point of OD is obtained by finding brightness pixel value based on average filtering. After that, OD diameter is measured from the detected optic disc boundary. The proposed scheme is validated on 30 healthy and glaucoma retinal fundus images from HRF database. The results are compared to the ground truth images. The proposed scheme obtains evaluation result (E) for healthy and glaucoma images is 0.23 and 0.21, respectively. These results indicate successful implementation of automated OD localisation by detecting OD centre point and determining OD diameter.